The Colloid Osmotic Pressure Across the Glycocalyx: Role of Interstitial Fluid Sub-Compartments in Trans-Vascular Fluid Exchange in Skeletal Muscle - Curry, Fitzroy E.; Michel, C. Charles (Frontiers in Cell and Developmental Biology, 2021)
The primary purpose of these investigations is to integrate our growing knowledge about the endothelial glycocalyx as a permeability and osmotic barrier into models of trans-vascular fluid exchange in whole organs. We describe changes in the colloid osmotic pressure difference for plasma proteins across the glycocalyx after an increase or decrease in capillary pressure. The composition of the fluid under the glycocalyx changes in step with capillary pressure whereas the composition of the interstitial fluid takes many hours to adjust to a change in vascular pressure. We use models where the fluid under the glycocalyx mixes with sub-compartments of the interstitial space whose volumes are defined from the ultrastructure of the inter-endothelial cleft and the histology of the tissue surrounding the capillaries. The initial protein composition in the sub-compartments is that during steady state filtration in the presence of a large pore pathway in parallel with the “small pore” glycocalyx pathway. Changes in the composition depend on the volume of the sub-compartment and the balance of convective and diffusive transport into and out of each sub-compartment. In skeletal muscle the simplest model assumes that the fluid under the glycocalyx mixes directly with a tissue sub-compartment with a volume less than 20% of the total skeletal muscle interstitial fluid volume. The model places limits on trans-vascular flows during transient filtration and reabsorption over periods of 30-60 minutes. The key assumption in this model is compromised when the resistance to diffusion between the base of the glycocalyx and the tissue sub-compartment accounts for more than 1% of the total resistance to diffusion across the endothelial barrier. It is well established that, in the steady state, there can be no reabsorption in tissue such as skeletal muscle. Our approach extends this idea to demonstrate that transient changes in vascular pressure favoring initial reabsorption from the interstitial fluid of skeletal muscle result in much less fluid exchange than is commonly assumed. Our approach should enable critical evaluations of the empirical models of trans-vascular fluid exchange being used in the clinic that do not account for the hydrostatic and colloid osmotic pressures across the glycocalyx.